Integration of Cooperation Development in Learning Planning to Realize Pancasila Student Profiles - Sejati, Andriyani Wahyu Puspo; Darsinah, D (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to analyze the learning implementation plan in developing cooperative attitudes and to identify various activities that foster collaboration in early childhood education as part of realizing the Pancasila Student Profile. Methodology: The research was conducted at Aisyiyah 5 Semanggi Kindergarten, Surakarta, using a qualitative descriptive approach. Data sources included teacher interviews and documents in the form of Daily Learning Implementation Plans (RPPH) from 9 teaching modules representing four sub-themes: 3 on “Myself,” 1 on “My Motherland,” 3 on “Environment,” and 2 on “My Needs.” Data collection techniques included interviews, observation, and documentation. Data were validated through triangulation and analyzed using content analysis techniques. Results: The analysis showed that from a total of 115 learning activities reviewed, 21.7% were found to have the potential to foster cooperative attitudes. These activities were mostly embedded in gross motor activities, games, micro and macro role-playing, play development, and collaborative cognitive and artistic exercises involving two or more children interacting with positive interdependence. Applications/Originality/Value: This research contributes to early childhood learning design by highlighting the integration of cooperative values into various learning activities. It provides practical references for educators in aligning instructional planning with the development of social skills and national character values such as cooperation as part of the Pancasila Student Profile.